Molecular characterization of pathogenic e. coli and staphylococcus aureus isolated from some fermented milk products by using PCR - Atef, Neven; Ibrahim, Mohamed; Sleim, Al-Shimaa A.; Abdel-Mageed, Abdel-Rahman (2017)
The objectives of this study were to investigate the prevalence of molecular character of Enteropathogenic E. coli and Staph. aureus in some fermented milk products by using multiplex PCR. A total of 120 fermented milk products represented as plain yoghurt and pasteurized yogurt (40 of each) from two trade companies and 40 samples of rayeb milk divided into pasteurized milk rayeb and Laban rayeb (20 of each). Bacteriological examination revealed that the incidence of E. coli was 40% (16), 30%(12), 55%(11), and 10%(2) for plain yogurt, pasteurized yoghurt, Laban rayeb and pasteurized milk rayeb, respectively, and for Staph. aureus was 5%(2) and 25%(5) for plain yogurt and Laban rayeb, respectively, while Staph. aureus could not be detected in both pasteurized yoghurt and pasteurized rayeb samples. Pathogenicity test for E. coli and Staph. aureus isolates revealed 5 isolates for each strain. E. coli and Staph. aureus isolates were subjected to PCR for detection of eaeA, STa , Stx1 and Stx2 gene from E. coli, and Sed, See, coa and mecA gene from Staph. aureus. Only Stx2 gene and STa gene were detected in E. coli strain isolated from plain yogurt and Laban rayeb samples respectively, and mecA and Sed genes were detected in Staph. aureus strain isolated from Laban rayeb. Generally, application and implementation of (HACCP) system as a hazards control system should be done in dairy processing plan prevention and to ensure a maximum safety to consumers.
Includes references.
Summary in Arabic
Keywords: Escherichia coli; Staphylococcus aureus; Fermented milk -- Microbiology; Yogurt -- Microbiology; Dairy products -- Rheology